2021
DOI: 10.3390/molecules26165055
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia Diterpenes: An Update of Isolation, Structure, Pharmacological Activities and Structure–Activity Relationship

Abstract: Euphorbia species have a rich history of ethnomedicinal use and ethnopharmacological applications in drug discovery. This is due to the presence of a wide range of diterpenes exhibiting great structural diversity and pharmacological activities. As a result, Euphorbia diterpenes have remained the focus of drug discovery investigations from natural products. The current review documents over 350 diterpenes, isolated from Euphorbia species, their structures, classification, biosynthetic pathways, and their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 110 publications
(470 reference statements)
0
19
0
Order By: Relevance
“…Thus, what is currently known is that possibly the structureactivity relationship of these diterpenes revealed that acetylation and esterification of hydroxyl groups, particularly at C-3 and C-8, positively affect these activities. 135 Due to the various substitution patterns in isolated ingenoltype diterpenoids, structure-activity relationships remain under investigation. The rigid ingenol scaffold conveys several structural features, including the 5-and 20-hydroxyl groups, which may be essential for biological activity.…”
Section: Diterpene Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, what is currently known is that possibly the structureactivity relationship of these diterpenes revealed that acetylation and esterification of hydroxyl groups, particularly at C-3 and C-8, positively affect these activities. 135 Due to the various substitution patterns in isolated ingenoltype diterpenoids, structure-activity relationships remain under investigation. The rigid ingenol scaffold conveys several structural features, including the 5-and 20-hydroxyl groups, which may be essential for biological activity.…”
Section: Diterpene Biological Activitymentioning
confidence: 99%
“…Thus, what is currently known is that possibly the structure–activity relationship of these diterpenes revealed that acetylation and esterification of hydroxyl groups, particularly at C-3 and C-8, positively affect these activities. 135…”
Section: Diterpenesmentioning
confidence: 99%
“…Ingol 7,8,12-triacetate 3-phenylacetate ( 1 ), ingol 7,8,12-triacetate 3-(4-methoxy-phenyl) acetate ( 2 ) and 8-methoxyingol 7,12-diacetate 3-phenylacetate ( 3 ) have the lathyrane skeleton, that is, tricyclic diterpenes with a 4/11/3-ring system, an epoxy functionality at C- 4 and C- 15 and a double bond between C- 5 and C- 6 ( Figure 3 ) [ 33 ], which precursors are most likely the ones just mentioned. Further, those ingol diterpenoids underwent redox, etherification and esterification modifications of the 5- and 11-membered rings ( Figure 3 ).…”
Section: Biosynthesis Of Diterpenes Triterpenes and Sterolsmentioning
confidence: 99%
“…However, the most representative and diverse class of Euphorbia secondary metabolites are undoubtedly diterpenes. A wide array of typical structural frameworks, from macrocyclic to polycyclic architectures, have been identified, including tiglianes, ingenanes, daphnanes, lathyranes, jatrophanes, and myrsinanes [ 4 ]. These compounds have been identified as the components mainly responsible for the potent skin-irritating and tumor-promoting effects associated with Euphorbia latex [ 5 ].…”
Section: Introductionmentioning
confidence: 99%